Постать А. Кримського крізь призму дискурсивного простору його листів до І. Франка - Космеда, Т. (Культура слова, 2021)
Дослідницький матеріал – фрагменти листів А. Кримського до І. Франка. У статті простежено особливості інтимізації персонального тексту, омовлення почуття поваги та любові з урахуванням дискурсивної своєрідності творця епістем,
особливостей його ідіостилю. Зосереджено увагу на таких
стилістичних явищах, як інтертекстуальність, моделювання оказіональних слів, уживання зменшено-пестливих форм,
актуалізація іншомовних украплень; синкретичне поєднання
характерних мовленнєвих жанрів; створення гібридних жанрових епістолярних зон; моделювання критично-інтимного
дискурсу; демонстрація високого рівня системи компетенцій
мовної особистості. Зроблено висновок, що А. Кримський у дискурсивному
просторі листування демонструє креативність і виразно
виявляє індивідуальний стиль, відображений і в його художньому та науковому дискурсі, що потребує подальшого дослідження. Linguistics of the XXI century focuses on ego-texts or personal
texts, the study of which allows a deeper understanding of the
language personality, the nature of the personal language space. The
purpose of this scientific research is to find out the originality of a
fragment of A. Krymskyi’s epistemes to I. Franko. As a result of the
analysis, it was found out that Franko is a person close to Krymskyi
in spirit. We trace the specifics of verbalization of intimacy (special
forms of treatment that vary depending on the level of expression of
feelings), the stipulation of respect and love, taking into account the
peculiarities of the discursive originality of the creator of epistemes
(intertextuality, tendency to model occasional words, use of reducedloving
forms, actualization of foreign inclusions). A. Krymskyi’s
private letters contain genre speech subspecies, among which
pity, complaint, justification, confession, approval, motivation,
compliment, request, offer, gratitude, etc. prevail. In these letters,
several genres are syncretically combined, creating hybrid genre
epistolary zones. In general, these letters are respectfully majestic
when the text concerns I. Franko, or ironically humorous when it
comes to the personality of A. Krymskyi himself. The author of
the letters models a kind of critical-intimate discourse, correctly
expressing remarks. The main purpose of these letters is to inform
about events, discuss everyday life, express emotions, tell about the
facts of the biography, convince of the correctness of their opinions,
critically point out certain scientific problems, set the addressee
to positive and fruitful cooperation. Among the stylistic features
of A. Krymskyi’s epistemes we single out (1) special honors or
respectfully friendly addresses; (2) the use of various speech egotext
subgenres with their peculiar application and the corresponding
dominant tone; (c) casual selection of language means, among
which there are idiostyle ones; (d) immediacy in the expression of
feelings; (e) ease of speech, sincerity. A. Krymskyi demonstrates
creativity and clearly shows the individual style, reflected in his
artistic and scientific discourse.